Hardware-assisted real-time operating system deployed on FPGA - Pereira, Jorge (2014)
Determinism and predictability are two de facto critical and demanded requirements in real-time embedded systems. As applications increase their functionality and complexity, real-time operating systems (RTOSs) come into play, and due to the complexity of the systems itself, not always is possible to keep the commitment with these requirements. In this paper we present a hybrid hardware/software real-time operating system approach, where system latency and predictability are improved by offloading critical run-time services to hardware. A field-programmable gate array (FPGA) is used to synthesize a MicroBlaze soft-core processor and the developed hardware accelerators, exploiting the point-to-point bus Fast Simplex Link (FSL) to tightly interconnect the customized hardware accelerators with the MicroBlaze soft-core processor